1921 Mo. Laws 691-92 - (:unkn) unknown (My University, 1921)
Weapons, Firearms: Regulation of Sale and Possession, § 1: No wholesaler or dealer therein shall have in his possession for the purpose of sale, or shall sell, any pistol, revolver, or other firearm of a size which may be concealed upon the person, which does not have plainly and permanently stamped ,upon the metallic portion thereof, the trademark or name of the maker, the model and the serial factory number thereof, which number shall not be the same as that of any other such weapon of the same model made by the same maker, and the maker, and no wholesale or retail dealer therein shall have in his possession for the purpose of sale, or shall sell, any such weapon unless he keep a full and complete record of such description of such weapon, the name and address of the person from whom purchased and to whom sold, the date of such purchase or sale, and in the' case of retailers the date of the permit and the name of the circuit clerk granting the same, which record shall be open to inspection at all times by any police officer or other peace officer of this state.
Keywords: COMMERCIAL SALES REGULATION